The Role of Parenting in Implementing Health Literacy in Early Childhood: A Case Study of Millennial Families in Tangerang Regency - Fitria Budi Utami; Yuli Rahmawati; Asep Supena (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
In Indonesia, literacy health is one of the keys to increasing public awareness of the importance of balanced nutrition and healthy lifestyles, especially in efforts to reduce the prevalence of stunting, wasting, underweight, and overweight in infants and toddlers in Indonesia. The research aims to explore role pattern foster millennial family in implementation literacy health in children age early in Tangerang Regency based on health literacy health. This is a case study aimed to explore the role of pattern foster family and wisdom local in promotion health public. The study is conducted on three millennial families in one village. who have children aged 2-3 years. The results show that literacy health play a role important in help individual understand risk health, comply treatment, as well as operate behaviour life Healthy. This in harmony with literature stating that factor environment and education influence behaviour parenting and literacy health. However, some respondents also rely on source information conventional, such as Integrated Health Service Post, shows that combination between digital and conventional media proven effective in distribution information health.